A escola do diabo Indígenas e capuchinhos italianos nos sertões da América (1680-1761) - Cruz, Carlos Henrique (Premio Istituto Sangalli per la storia religiosa, 2019)
The book discusses the work of Italian Capuchins in the face of American otherness, especially in the catechism of Indians and mestizos accused of being devil's wizards. The friars faced a crisis in missionary optimism in the face of an alleged indigenous resistance to Christianity or to European social rules. The Portuguese colonial sources reveal evangelization as a field of dispute between the friars, the natives and the colonists, motivating daily conflicts, also encouraging changes in the social and symbolic traditions inside or near the missions. The indigenous people were not passive subjects in the process, contradicting the missionaries for the determination with which, supposedly, they practiced their "gentile" customs and rites. The documentation gathered adds important information to the study of indigenous peoples in contact with Capuchins in the inner territories of Portuguese America.